Via caritatis - Hastetter, Michaela C. (Marriage, families & spirituality, 2017)
Like all pastoral activities of the church, the pastoral care of divorcees who are remarried falls under the command of love of neighbour. Pope Francis pointedly reformulated this insight in Amoris laetitia (cf. AL 306). In this paper the theological basis of various emphases is examined in the pastoral care of remarried divorcees based on charity as found in the three major Christian denominations (Orthodox, Protestant and Catholic) and compared in their respective practical outcomes. The rejection of the sacramental nature of matrimony on the part of Protestants, with the consequent unlimited permission to remarry, finds its practical-pastoral expression not only in occasional liturgical services for those who are divorced but even in the incorporation of the possibility of divorce into the liturgical form of marriage itself. For the Orthodox, a limited possibility of remarriage after divorce is generally permitted and is characterized by repentance and penance. In this case, the pastoral accompaniment of remarried divorcees remains tied to the principle of oikonomia and is justified in terms of the therapeutic care of souls. In the Catholic Church, the pastoral care of remarried divorcees is based on the indissolubility of marriage. Two different pastoral approaches are elaborated here: the consequent non-admission of remarried divorcees to the sacraments and marriage ministry as a pastoral of faith on the one hand side, and on the other hand a more open practice in the admission to the sacraments. Against this background, it is discussed where to situate the position of Amoris laetitia concerning the pastoral care of remarried divorcees and what its ecumenical relevance is.